The effects of partial bilateral lesioning of substantia nigra in a genetic absence epilepsy rat model - (:unkn) unknown (My University, 2002)
Objective: "Genetic Absence Epilepsy Rats from Strasbourg" (GAERS), an inbred Wistar strain, serve as an experimental venue. These rats generate spontaneous spike-and-wave discharges (SWD) and have increased γ-aminobutyric acid (GABA) levels in the ventrolateral thalamus (VLT). Recently, substantia nigra pars reticulata (SNpr) was reported to act as an endogeneous inhibitory mechanism in the generation, onset and maintenance of various types of seizures. The presence of tonic control exerted by SNpr in absence seizures should also be tested in GAERS. Methods: In this current study, GABA and L-glutamic acid release in VLT of GAERS with partial bilateral electrolytic lesions of SNpr was evaluated by using microdialysis technique with fluorescent detection. Results: GABA levels in VLT were 0.12±0.04 μM and 0.24±0.08 μM in sham-lesioned and SNpr-lesioned GAERS, respectively. L-glutamic acid level was found to be 0.41 5±0.150 μM in sham-lesioned group and 0.324±0.094 μM in SNpr-lesioned GAERS. Statistical analysis revealed no significant difference between sham-lesioned and SNpr-lesioned rats. The number and the duration of SWD were also similar in two groups. Conclusion: These findings show that SNpr does not exert a tonic control in GAERS and we assume that intact SNpr acts as a site that may exert an inhibition on target structures when activated in GAERS.
Keywords: Absence epilepsy; GABA γ-aminobutyric acid); GAERS (Genetic Absence Epilepsy Rats from Strasbourg); Microdialysis; Nigral control of epilepsy; Substantia nigra; Ventrolateral thalamus